Pelatihan Bantuan Hidup Dasar (BHD) Bagi Jemaat Gereja HKBP Jl. Uskup Agung Sugiopranoto Medan: Upaya Peningkatan Pengetahuan dan Keterampilan Pertolongan Pertama pada Kondisi Gawat Darurat - Dwi Lunarta Siahaan; Owen Sitompul; Marolop Hutapea; Joslouis Hutagaol; Horas Rajagukguk; Rebecca Rumesty Lamtiar; Jadeny Sinatra; Alexander P. Marpaung; Novrina Situmorang; Maesstro B. U. Simanjuntak; Harry Butar-butar; Ivonne R.V.O. Situmeang; Evirosa J. Simanjuntak; Inda M.H. Sinaga; Julenda I. Sebayang; Sanggam B. Hutagalung; Irene R. T. Damanik; Adrian Khu; Hanjaya Hanjaya; Nova Feronika Rajagukguk; Jekson M. Siahaan; Hadyanto Lim; Paul S. M. L. Tobing; Surjadi Rimbun; Ronald T.H. Tambunan; Juliyanti Tarigan; Kezia Stephanie S.; Karen Natalie S. (Universitas Methodist Indonesia, 2025)
Sudden death due to cardiac arrest and respiratory failure frequently occurs in the community, including in public places and houses of worship. Basic Life Support (BLS) is a simple yet crucial initial action to preserve life before advanced medical care is available. This community service activity was part of the HKBP Gotilon Festival 2025, organized in collaboration between the HKBP Church Jl. Uskup Agung Sugiopranoto Medan, Medical Faculty of Universitas Methodist Indonesia, Medical Faculty of Universitas HKBP Nommensen, and supported by the Indonesian Cardiovascular Specialist Association (PERKI) as experts. The program aimed to improve the knowledge and skills of the congregation of the HKBP Church in performing BLS. The methods included health education on the basic concepts of BLS, demonstration of cardiopulmonary resuscitation (CPR), and hands-on practice using mannequins. The results showed an increase in participants understanding of emergency response steps as well as their ability to perform CPR correctly. This activity is expected to raise community awareness of the importance of BLS skills and to equip them with the capability to provide initial assistance in emergency situations.